ANALYZING THE KEY ELEMENTS OF HIGH-QUALITY ABSTRACTS: A COMPREHENSIVE ACADEMIC DISCOURSE STUDY OF ENGLISH EDUCATION - Santoso, Kusumo Hadi; Arifani, Yudhi; Maruf, Nirwanto (English Review: Journal of English Education, 2024)
This study aims to explore the Rhetorical moves and use of Metadiscourse in student abstracts from the English Education program at Universitas PGRI Ronggolawe, Tuban. The sample consists of 17 abstracts submitted by English Education students from the 2023 batch of the program. This Research uses mixed methods for the methodology, the quantitative analysis focused on frequency counts, descriptive statistics, and correlation analyses, while the qualitative analysis explored the functional roles of these elements in enhancing clarity, coherence, and reader engagement. The qualitative analysis revealed that students who used more transitions and frame markers produced more coherent and structured abstracts. Students who used a variety of interactive and interactional markers, such as transitions, frame markers, and self-mentions to balance confidence with caution and engage the reader, were more likely to produce more coherent, clear, and engaging abstracts than those who did not. The findings suggest that students would benefit from explicit instruction on the role of Metadiscourse in academic writing, particularly in how to use hedges, boosters, and self-mentions to balance confidence with caution.